Fractional Brownian motion (approximations of fBm) : weak and strong approximations and projections /: weak and strong approximations and projections. (2019) - Banna, Oksana; Mishura, I︠U︡lii︠a︡ S; Ralchenko, Kostiantyn
No abstract available